Wound healing in rabbit corneas after flapless refractive lenticule extraction with a 345 nm ultraviolet femtosecond laser - Hammer, Christian M.; Petsch, Corinna; Klenke, Joerg; Skerl, Katrin; Wuellner, Christian; Donitzky, Christof; Paulsen, Friedrich; Scholz, Michael; Seiler, Theo; Kruse, Friedrich; Menzel-Severing, Johannes (Journal of Cataract and Refractive Surgery, 2017)
PURPOSE: To characterize corneal wound healing in a rabbit model after flapless refractive lenticule extraction with a 345 nm ultraviolet femtosecond laser. SETTING: Departments of Ophthalmology and Anatomy II, University of Erlangen-Nürnberg and Wavelight GmbH, Erlangen, Germany. DESIGN: Experimental study. METHODS: Flapless refractive lenticule extraction was performed in 1 eye each of 20 New Zealand white rabbits (-5.0 diopters). Groups of 4 animals were euthanized after 48 hours, 1 week, 2 weeks, 4 weeks, and 3 months, respectively. Corneal samples were prepared for histology and fluorescence microscopy. To assess corneal cell death, proliferation, and myofibroblastic transdifferentiation, terminal uridine deoxynucleotidyl nick end-labeling (TUNEL) assay as well as immunostaining for Ki67 and α-smooth muscle actin (αSMA) were performed on sagittal cryosections. RESULTS: Histology revealed a zone of keratocyte depletion with a thickness of approximately 50 μm around the extraction site. At 48 hours, pronounced TUNEL staining of keratocytes was detected around the interface (159.9 cells/mm ± 18.4 [SD]), which steadily decreased to 74.9 ± 19.8 cells/mm at 1 week and 5.7 ± 4.8 cells/mm at 2 weeks. Ki67 staining of keratocytes was evident at 48 hours (10.0 ± 3.8 cells/mm), which then decreased at 1 week (5.2 ± 1.7 cells/mm) and 2 weeks (0.4 ± 0.5 cells/mm). From 4 weeks onward, no TUNEL or Ki67 staining was detected. The corneal stroma was αSMA-negative at all timepoints. CONCLUSION: Application of the 345 nm laser showed no signs of problematic repair processes in the cornea, which supports the initiation of the clinical phase.
EVALuna2:35326